XPS IDENTIFICATION OF BULK HOLE DEFECTS AND ITINERANT FE 3D ELECTRONS IN NATURAL TROILITE (FES) - Skinner W.M.; Nesbitt H.W.; Pratt A.R. (My University, 2004)
XPS measurements have been made of vacuum-fractured monoclinic pyrrhotite and troilite that highlight sulfur coordination (S 2p) and iron electronic state (Fe 2p) differences between these two minerals as a result of iron lattice site occupancy. Metal-like Fe states are observed in the Fe 2p spectrum of troilite due to increased occupancy of Fe lattice sites and increased Fe-Fe 3d orbital interaction within the constraints of the mineral structure. Additional electron population near the top of the troilite valence band is confirmed by XPS measurement. These results provide comprehensive experimental evidence for itinerent 3d electrons in the natural iron sulfides.
Keywords: troilite